PULMONARY TUBERCULOSIS IN DIABETES PATIENTS (BASED ON AUTOPSY PROTOCOLS) - M. V. Belosokhov; E. L. Kаzаchkov (Туберкулез и болезни лёгких)
The objective of the study: to study the specific features of pulmonary tuberculosis in diabetes patients based on the autopsy data.Subjects and methods: Autopsy protocols of pulmonary tuberculosis cases (N=1045) were studied, among them there were some patients with concurrent diabetes (N = 34).Results: the part of those with concurrent tuberculosis and diabetes made 3.3% among died respiratory tuberculosis patients. Women confidently prevailed among those with concurrent tuberculosis and diabetes (38.2% versus 15.3% in the group of patients without diabetes, p = 0.0003). Respective the form of tuberculosis, the differences were not significant, as well as the frequency of acute progression. Co-morbidity in the patients with diabetes according to comorbidity index was more frequent (diabetes was not included) versus patients without diabetes (p = 0.000225). The main cause of death in both groups was pulmonary heart disease.